MANAGEMENT OF FOREIGN INVESTMENTS IN KAZAKHSTAN (Journal of Economic Research & Business Administration, 2017)
Basic trends in the development of the Kazakhstan economy in the medium and long term determine the need to attract significant amounts of external investment. A growing market economy needs resources to implement strategic investment projects, carry out structural reforms, and update productive capital. In the conditions of an open market economy, the concept of «investment» acquires a certain specificity. In contrast to the study of investment problems in the administrative and command system of the economy, when a simplified scheme for allocating capital investments operated, the issues of attracting foreign capital and regulating its activities are now becoming increasingly complex and multifaceted. In particular, the processes of attracting and operating foreign capital in the Kazakhstan economy require taking into account the factors shaping the investment climate. To the main factors determining the formation and development of foreign investment activities in the territory of the host state, such as political and economic stability, the state and degree of development of the regulatory and legislative framework, the level of development of market infrastructure. Financial investment problems involved many economists both foreign and domestic: Seytkazieva A.M., Nurlanova N.K., Mamyrov N.K., Dankov A.N., Bart J. and others.